A green high-initiation-power primary explosive: synthesis, 3D structure and energetic properties of dipotassium 3, 4-bis(3-dinitromethylfurazan-4-oxy)furazan1. Issue 71 (2nd August 2015) - Zhai, Lianjie; Fan, Xuezhong; Wang, Bozhou; Bi, Fuqiang; Li, Yanan; Zhu, Yanlong
<x xml:space="preserve">Abstract</x> A environmentally friendly 3D primary explosive potassium 3, 4-bis(3-dinitromethylfurazan-4-oxy)furazan with high initiation power was fully investigated.